Interlanguage Produced by the 8th Semester Students of English Literature Study Program at Stikubank University - Gunawan, Patricia Putri; Rustipa, Katharina (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
This research is aimed to find the types and factors of interlanguage using descriptive method. The researcher used the theory from Xin Wang and Lingling Fan (2020) about interlanguage. The data is gathered from the students of eighth semester of English Literature in University of Stikubank. The procedures used to gather the data are: interviewing the participants, asking to do the monologue, recording the monologue, listening the English monologue, transcribing the monologue, segmented the data into unit of analysis. Eight of eight students made mistakes. The student initialed “U” made 48% mistakes, and the student initialed “D” made 1% mistake. Overgeneralization became the most mistake they made because it belongs to grammatical structurures that does not exist in first language